ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERINGKAT OBLIGASI PADA PERUSAHAAN-PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2018 - Tannia, Tannia; Aryanilo, Aryanilo; Edward, Edward (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2020)
Bond is one financial instrument that are interest to investors, in making decisions to buy bond the rating of bond can be the basis to buy bonds. The rating of bond can be seen from the ranking institution like PEFINDO. This study was conducted to analyze factor that influence the rating of bond in banking companies listed on Indonesia Stock Exchange period 2015 to 2018. Suspected factor that influence the rating of bonds is Capitalization, Liquidity, Profitability. Research Method used Multiple Linear Regression, hypothesis testing using F test and T test with level of significance 5% (Î±= 0,05). Type data that used is secondary data. In this study the sample is 22 banking companies Data was obtained from Indonesia Stock Exchange official site. The sampling technique is determined using targeted sampling (purposive sampling). The result form hypothesis testing is caplitalization, liquidity, profitability not affect the rating of bonds partially and simultaneously.